EDUCATION: science policy studies: rebirth of an academic centre (2003)
When the Jawaharlal Nehru University was founded in 1970, one of the earliest decisions taken by its executive council was to set up a Centre for Studies in Science Policy (CSSP) in the School of Social Sciences. However, there was a freeze in admission of students in the late 1970s and the centre remained in suspended animation for a decade and a half. The centre was revived in 1996 andhas got into its stride in the last three years. The revival, rebuilding and accelerated development of the CSSP augurs well for the S and T system in the country. - Reproduced.
Keywords: Social research; Social policy